2021
DOI: 10.1002/alr.22758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olfactory training on posttraumatic olfactory dysfunction: a systematic review and meta‐analysis

Abstract: Background Posttraumatic olfactory dysfunction is a clinical challenge due to refractory characteristics and limited therapeutic options. Olfactory training has been proved to be effective for olfactory dysfunction with varied etiologies. We pooled existing studies to evaluate the effects of olfactory training in patients with posttraumatic olfactory dysfunction. Methods A systematic literature review using PubMed, Embase, Cochrane Library, and Web of Science was conducted to identify studies assessing olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Although patients with post-infectious olfactory dysfunctions experienced significant improvement of olfaction, a mean increase of 4.47 in TDI scores did not reach the minimal clinically important difference of 5.5 after treatment with short-term systemic steroids (Schriever et al, 2012). Our recent meta-analysis of the effects of olfactory training on post-traumatic olfactory dysfunction showed that post-traumatic patients would achieve clinically significant results after olfactory training with a mean increase of TDI score of 4.61 (Huang et al, 2021). The different treatment response of the odor threshold between post-traumatic and post-infectious olfactory dysfunction reveals different plasticity of the peripheral olfactory function after olfactory training.…”
Section: Characteristics Of Olfactory Impairment In Post-infectious Amentioning
confidence: 91%
“…Although patients with post-infectious olfactory dysfunctions experienced significant improvement of olfaction, a mean increase of 4.47 in TDI scores did not reach the minimal clinically important difference of 5.5 after treatment with short-term systemic steroids (Schriever et al, 2012). Our recent meta-analysis of the effects of olfactory training on post-traumatic olfactory dysfunction showed that post-traumatic patients would achieve clinically significant results after olfactory training with a mean increase of TDI score of 4.61 (Huang et al, 2021). The different treatment response of the odor threshold between post-traumatic and post-infectious olfactory dysfunction reveals different plasticity of the peripheral olfactory function after olfactory training.…”
Section: Characteristics Of Olfactory Impairment In Post-infectious Amentioning
confidence: 91%
“…The data indicated that OT could improve the ability of discrimination and identification of odors in patients with post-traumatic olfactory disorders within 8 months. 66 After 6 months of OT, odor sensitivity could be improved slightly but the ability of odor identification remained unchanged. 67 The authors postulated that the reasons for these inconsistent results might be due to differences in OT and olfactory-testing methods between institutions.…”
Section: Research Progress In Otmentioning
confidence: 97%
“…With regard to treatment of impaired olfaction, a systematic review with meta-analysis evaluating the efficacy of olfactory training in the setting of posttraumatic olfactory dysfunction demonstrated a mean Sniffin' Stick threshold, discrimination, and identification (TDI) score increase of 4.61, suggesting that olfactory training could represent a promising modality for the treatment of posttraumatic olfactory dysfunction, but high-quality and controlled studies are needed. 38 Two unique studies evaluated the milieu of the olfactory cleft and olfactory function in CRS patients. A case-control pilot study by Soler et al 39 assessed specific mucous proteins and the proteomic profile of the olfactory cleft of using hierarchical clustering and bioinformatic analysis.…”
Section: Olfaction and Gustationmentioning
confidence: 99%
“…evaluated the psychometric properties of the Brief Questionnaire of Olfactory Disorders–Negative Statements, an abbreviated version of the parent survey, and demonstrated minimal information loss and excellent external predictive utility when compared to the original questionnaire when used in patients with CRS. With regard to treatment of impaired olfaction, a systematic review with meta‐analysis evaluating the efficacy of olfactory training in the setting of posttraumatic olfactory dysfunction demonstrated a mean Sniffin’ Stick threshold, discrimination, and identification (TDI) score increase of 4.61, suggesting that olfactory training could represent a promising modality for the treatment of posttraumatic olfactory dysfunction, but high‐quality and controlled studies are needed 38 …”
Section: Olfaction and Gustationmentioning
confidence: 99%